Teachers Perception Of Instructional Technology Integration Into English Language Learning - Hidayat, Faridh; Tanduklangi, Amri; Badara, Aris (Journal of Language Education and Educational Technology (JLEET), 2018)
This research aims to describe teachers’ perceptions of instructional technology integrating into English language learning. Five aspects are studied: teachers’ perception, competency technology, attitude, experience and barrier of instructional technology integrating into English language learning. This study used descriptive. The population of study was 43 respondents. A sample consisting of 21 teachers were randomly selected from English teachers of SMK Kendari. The result of data analysis showed numerous conclusions. First, most of English teachers were proficient using technology computer. The second, most of English teachers had a positive perception toward instructional technology into English language learning. The third, most of English teachers had a positive attitude toward instructional technology into English language learning, the fourth, the English teachers were sometime and seldom in integrating instructional technology into English language learning, the fifth, there was some barrier in integrating instructional technology into English language learning. It means that even though teachers have a positive perception, a positive attitude of instructional technology integrating into English language learning, unfortunately they sometime and seldom to use technology into English language learning because of same problems namely, they lack of technical support and insufficient internet speed, most parents not in favour to use technology in term of financial, and lack of content technology for teaching